Sustainability of National Development Program During Transition of Leadership In Indonesia - Firdaus Arifin (Sekolah Tinggi Hukum Bandung, 2024)
The sustainability of national development programs in Indonesia is often hindered by leadership transitions, which create uncertainty in the implementation of long-term policies. This study aims to analyze the weaknesses of the existing legal framework, particularly Law No. 59 of 2024 concerning the National Long-Term Development Plan (RPJPN), in ensuring the continuity of development programs amidst political dynamics. A normative approach with qualitative juridical analysis was employed, examining relevant legislation and literature. The findings reveal that the current legal framework needs to be more robust to protect strategic programs from policy changes caused by government transitions. Additionally, the lack of flexibility within the legal instruments makes it difficult to adapt to political changes. This study recommends more responsive and adaptive legal reforms and enhances synergy between central and regional governments to ensure policy stability. These findings contribute to the theoretical development of development law and have practical implications for policymakers in Indonesia, particularly in designing a more robust and stable legal framework to support long-term development.